Strategic Communication in Public Relations Practices: A Bibliometric Analysis Based on Scopus Database from 2015 to 2025 - Nurul Fadhillah; Suwandi Sumartias; Aang Koswara (INJECT (Interdisciplinary Journal of Communication), 2025)
Researchers systematically analyze studies on strategic communication in public relations through a bibliometric review. The aim is to determine the current state and development of research on strategic communication, especially in the context of Public Relations. This research contributes to a broader, more precise understanding of the research landscape on strategic communication and to the identification of keyword trends for future research. The research employed a qualitative approach, along with bibliometric and thematic analyses, to review the literature on strategic communication in the context of public relations. The researcher collected scientific articles on strategic communication in the context of public relations through the Scopus database. The finding that attracts the researcher's attention is the annual growth rate of 2.54% suggests that academic attention remains relatively limited, which consequently impacts the field's growth trajectory. Another finding of this research is the significant evolution in research topics occurred during the period from 2015 to 2025. While previous studies positioned social media and digital technology as 'hot topics' for future inquiry, this study finds that both have since become mature and developing fields. The high density of these keywords indicates that scholars are no longer merely exploring the definitions of social media but are instead investigating in depth how it functions strategically to shape public opinion. The evolution of research topics confirms that the profession is moving beyond technician roles toward strategic management functions, where PR practitioners are increasingly involved in high-level organizational decision-making. The research over the past decade has primarily focused on the corporate context. Consequently, we suggest exploring how non-corporate sectors, such as NGOs, government agencies, and advocacy groups, adopt digital strategic communication practices to achieve their organizational goals.